Caracterização fenotípica e molecular dos mecanismos de resistência aos beta-lactâmicos em linhagens clínicas de Klebsiella pneumoniae isoladas do Amazonas - Souza, Rosineide Cardoso de (2018)
Klebsiella pneumoniae resistant to beta-lactams are present in hospitals worldwide and reduce treatment alternatives. In this study, 40 K. pneumoniae isolates were characterized. All of them were resistant to beta-lactam antibiotics and classified as multidrug resistant. Among these, eight isolates were resistant to carbapenems and six of which had the gene blaKPC-2, encoding the enzyme Klebsiella pneumoniae carbapenemase (KPC). The blaTEM and blaCTX-M genes were found in 80% of the samples. The 40 isolates were grouped into 12 pulses (A to L) according to the genetic similarity determined by the DNA macro-restriction followed by pulsed-field gel electrophoresis. A total of 20 isolates were classified as pulsotype A, which was subdivided into 13 subtypes (A1 to A13), with subtype A1 being the most prevalent. Representatives of pulsotype A belong to the ST11, clonal complex CC258. In this study, we identified four new STs: ST2540, ST2308, ST2258, and ST2307. AMKP5 and AMKP2, belonging to subtypes A7 and A8, respectively, are resistant to carbapenems but did not present the blaKPC gene. Sequencing of the AMKP5 genome indicated mutations in the C-terminal region of the OmpK36 porin which may alter the entry of carbapenems into the cell. Genome sequencing of the AMKP10 isolate identified the plasmid pAMKP10, with 48.454 bp belonging to the IncX5 incompatibility group. In this plasmid, the blaKPC-2 gene was found in a non-Tn4401 genetic element (NTEKPC) containing tnpA-ISEc63-like / tnpR-Tn3 / tnpA-ISKpn27 / blaKPC-2 / ΔISKpn6, based on Tn1722. All isolates with the blaKPC-2 gene had the same plasmid. Conjugation of this plasmid to Escherichia coli J53 occurred from ST11 isolates with low conjugation frequencies (8.23 x 10-12 to 1.31 x 10-7) resulting in resistance to carbapenems. Finally, the outbreak of carbapenem-resistant K. pneumoniae resistant of this Amazonian hospital involved the transfer of the NTEKPC-containing pAMKP10 between two lineages (ST11 and ST2302) but was largely due to the clonal dissemination of the ST11 endemic lineage.